Sustainable development - Vrečko Ilc, Blaž (Journal of comparative politics, 2019)
The article interrogates sustainable development as the dominant presumably alternative paradigm of development and functioning of societies that declaratively transcends the ecological and societal limits of the older models. It argues that the dominant understanding of sustainable development that promotes limited incremental changes to the capitalist development model can best be understood as the result of its gradual systematic co-optation and integration into the dominant neoliberal governmentality at the global and local levels. By analysing the gradual neoliberalization of sustainable development in the global and the Slovenian context it argues that these contexts are interdependent concerning the consolidation and resilience of the neoliberal vision of sustainable development in the face of multiple and multidimensional economic and environmental crises. By specifically focusing on the case of Slovenia it demonstrates and reflects on the crucial role of actors that formally and informally represent the public interest such as the state and the organized civil society in re-legitimizing and upholding the neoliberal vision(s) of sustainable development in the context of crises.
Keywords: Civil society; Civilna družba; Neoliberalism; Neoliberalizem; Sustainable development; Trajnostni razvoj